2020
DOI: 10.3390/nu12061873
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect, Rheological Properties and α-Amylase Resistance of a New Mixed Starch and Xanthan Gum Thickener on Four Different Phenotypes of Patients with Oropharyngeal Dysphagia

Abstract: Thickened fluids are a therapeutic strategy for oropharyngeal dysphagia (OD). However, its therapeutic effect among different phenotypes of OD patients has not yet been compared. We aimed to assess the therapeutic effect and α-amylase resistance of a mixed gum/starch thickener [Fresubin Clear Thickener® (FCT)] on four phenotypes of OD patients: G1) 36 older; G2) 31 head/neck cancer (HNC); G3) 30 Parkinson’s disease; and G4) 31 chronic post-stroke. Therapeutic effect of FCT was assessed during videofluoroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 38 publications
1
56
0
Order By: Relevance
“…Our analysis showed an increase in piecemeal deglutition and pooling of oral and pharyngeal residue at the highest viscosity level assessed in our study (4000 mPa·s). In contrast, in a previous study of patients with OD and PD carried out with a mixed-composition thickener (with a high resistance to amylase), the viscosity safety threshold was reported to be maximal at 1000 mPa·s without increasing pharyngeal residue [ 26 ]. Further viscosity levels needs to be assessed to determine the therapeutic range and the optimal doses for each thickener.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our analysis showed an increase in piecemeal deglutition and pooling of oral and pharyngeal residue at the highest viscosity level assessed in our study (4000 mPa·s). In contrast, in a previous study of patients with OD and PD carried out with a mixed-composition thickener (with a high resistance to amylase), the viscosity safety threshold was reported to be maximal at 1000 mPa·s without increasing pharyngeal residue [ 26 ]. Further viscosity levels needs to be assessed to determine the therapeutic range and the optimal doses for each thickener.…”
Section: Discussionmentioning
confidence: 87%
“…Studies have reported various findings, for instance, that pudding-thick fluids compared to liquids increased swallow safety, but also increased transit time and the number of tongue pumps [ 22 ]; that a jelly consistency avoided aspiration [ 23 ]; and that aspiration avoidance occurred most often with honey-thickened liquids, followed by nectar-thickened liquids and chin-down posture [ 24 ], while none of those interventions influenced pneumonia incidence [ 25 ]. A more recent study has accurately described the therapeutic shear viscosity range (mPa·s) for patients with PD and OD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To develop a nutritional plan for older patients with OD that safely meets the main nutritional and hydration requirements and is palatable, we used two caloric/protein enriched diets for normal/at risk nutritional status vs. malnourished patients based on a previous study [ 2 ] using the Mini Nutritional Assessment (MNA ® ); two levels of viscosity for a safe fluid adaptation based on previous studies [ 6 , 26 ] using the V-VST and videofluoroscopy [ 27 ] and two levels of food texture—thick puree and fork mashable—for solid foods from the BDA food texture classification [ 28 ] and as commonly prescribed in our clinical practice. Patients will be designated the correct diet according to their MNA, V-VST, and chewing ability results.…”
Section: Methodsmentioning
confidence: 99%
“…(b) Selection of the bolus volume and viscosity. Thin liquids (water) and two levels of thickened fluids, 250 mPa·s and 800 mPa·s, were selected according to our previous studies assessing the therapeutic effect of fluid thickening in up to seven different levels of viscosity for this study [ 6 , 26 ]. Patients with OD will be prescribed the appropriate viscosity level according to the results of the V-VST [ 27 ], a validated bedside clinical test with optimal psychometric properties [ 32 ] that can select the optimal bolus volume (5, 10, or 20 mL) and viscosity to provide the safest and most efficacious swallow [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This can manifest, for example, as improving: (i) the bolus formation [ 264 ], (ii) impaired oropharyngeal bolus propulsion following treatment for oropharyngeal cancer at subsites such as the tongue base, pharyngeal wall, and soft palate or (iii) aspiration due to impaired upper respiratory tract closure and sensorial feedback in case of laryngeal dysfunction following (C)RT or partial laryngectomy. Nonetheless, there is a need for research to establish the ‘optimal’ viscosity levels to prevent aspiration and improve the safety and efficiency of oral intake for HNC patients [ 154 , 265 ]. Thickened fluids and altered consistency foods can also impact negatively on HRQOL (see " Psychosocial impact " section).…”
Section: Oropharyngeal Dysphagia Treatment In Head and Neck Cancermentioning
confidence: 99%